Concentration of heavy metal (Cd, Pb, Ni, Hg) in muscle, gill and liver tissues of Barbus xanthopterus in Karoon River - A. Askary Sary; M. Khodadadi; M. Mohammadi email (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2011)
We determined bioaccumulation of heavy metals (Cd, Pb, Ni and Hg) in the muscle, gill and liver organs of Barbus xanthopterus in summer 2009 in Karoon River, south west of Iran. Gill net was used to sample 48 random size fish specimens from Karoon River downward of Ahwaz city (Shekariyeh 3 village). The tissues were extracted and the elements were determined using atomic absorption spectrophotometer. Concentrations of heavy metals Cd, Pb, Ni , Hg in muscle tissue of Barbus xanthopterus were 1.679, 2.37, 1.16, 1.29mg/kg dry wt and in gill were 2.17, 2.92, 1.44, 1.34mg/kg dry wt and in liver were 1.92, 2.79, 1.31, 1.43mg/kg dry wt, respectively. All the results were statistically significant (P 0.05). The concentrations of heavy metals were higher than standards of the World Health Organization (WHO) in the muscle tissue of Barbus xanthopterus in Karoon River.